Crystal structure of 1-(2-cyanobenzyl)-3-cyano-4-phenyl-4-(2-cyanobenzyl)-1,4-dihydropyridine monohydrate, C56H42N8O - Li Yi-Da; Song Zhi-Qiang; Yue Zhi-Wei; Zhong Qi-Di; Qi Ya-Juan (Zeitschrift für Kristallographie - New Crystal Structures)
C56H42N8O, orthorhombic, Pbcn (no. 60), a = 17.885(3) Å, b = 15.647(2) Å, c = 16.189(2) Å, V = 4530.4(11) Å3, Z = 4, Rgt(F) = 0.0464, wRref(F2) = 0.1219, T = 296.15 K.